‘No Migration, No Gender, No War’: Contradictions and Paradox in Hungarian Migration Discourse - Bradford Simon; Cullen Fin (Politics in Central Europe)
The Hungarian Government’s long -standing politicisation of migration has recently become more complex. Two factors are particularly important here. First, following Russia’s war on Ukraine, over 60,000 refugees have arrived in Hungary seeking temporary protection. Second, Hungary’s FDI -based growth model and the country’s integration into global value -chains has exposed serious labour shortages. Hungary’s prime minister recently indicated the need for 500,000 new workers in the next two years. New government legislation now allows ‘third country’ nationals residence in Hungary as ‘guestworkers’ under strict conditions. More than 100,000 foreign workers are now in employment. The article explores contradictions between politicised anti -migrant discourse, the arrival of Ukrainian refugees and the introduction of guestworkers into the Hungarian labour market. It draws on qualitative data analysis including political speeches, social media postings and visual images. The article concludes by suggesting that Hungary can be understood as currently caught in a paradox between national economic imperatives on one hand and domestic political and public demands for the preservation of national identity on the other.